Multiple antibiotic resistance (MAR), plasmid profiles, and DNA polymorphisms among Vibrio vulnificus isolates - Al-Dulaimi, Mohammed M. Kurdi; Abd Mutalib, Sahilah; Abd Ghani, Maa'ruf; Mohd Zaini, Nurul Aqilah; Ariffin, Ahmad Azuhairi (MDPI, 2019)
Sixty strains (n = 60) of Vibrio vulnificus were examined for their multiple antibiotic resistance (MAR) index, plasmid profiles, and DNA polymorphisms. Thirty-seven strains (n = 37) were isolated from cockles (Anadara granosa) in Malaysia, while 23 (n = 23) isolates were isolated from clams (Mercenaria mercenaria) in Qatar. All isolates were resistant to two or more of the antibiotics tested, with the most common resistances were demonstrated towards penicillin (93%), ampicillin (70%), cephalothin (65%), clindamycin (66%), vancomycin (64%), and erythromycin (51%). The antibiotic that experienced the least resistance was kanamycin (6%), and all isolates were susceptible to cefoperazone, streptomycin, and tetracycline. The MAR index for the V. vulnificus isolated from Malaysia and Qatar, possessed similar values which ranged from 0.2 to 0.7, respectively. Plasmid analysis demonstrated that 65% of V. vulnificus strains harbored plasmids, while 35% were not. Nineteen (P1–P19) plasmids profiles were observed. No specific cluster or group was observed although they were isolated from different sample sources and locations by phylogenetic analysis using GelCompar II software at an 80% similarity level. Results demonstrated the high MAR index and genomic heterogeneity of V. vulnificus, which are of great concern to the human health of those who have consumed cockles and clams from the study area.